Bahan Ajar Interaktif Berbasis Open Educational Resources untuk Meningkatkan Hasil Belajar Kognitif Siswa Kelas V Sekolah Dasar - Trisnawati, Uma Fadhila; Supriyono, Supriyono; Kusmawan, Udan (JOEAI (Journal of Education and Instruction), 2025)
This study aims to develop OER-based interactive teaching materials, assess their feasibility, and evaluate their effectiveness in fostering harmony in ecosystem materials for fifth-grade elementary school students. This study employs a Research and Development (R&D) design based on the Borg & Gall research and development model. The research instruments include tests, questionnaire validation, student response questionnaires, observation sheets, and interviews. The results of the study indicate that OER-based interactive teaching materials developed in digital form and equipped with teacher usage instructions are declared feasible based on the assessment of material experts (obtaining a score of 73 out of a maximum score of 80), media experts (obtaining a score of 75 out of a maximum score of 80), practitioners (receiving a score of 39 and 38 out of a maximum score of 40), and policy makers (obtaining a score of 39 out of a maximum score of 40). OER-based interactive teaching materials are declared effective in improving cognitive learning outcomes of fifth-grade elementary school students. The results of the independent-samples t-test showed that the posttest scores of the experimental and control groups, with a significance value of 0.000 < 0.05, indicated a significant difference between the groups. The average posttest score for the experimental group (90.45) was higher than that of the control group (77.72). In conclusion, the OER-based interactive teaching material on harmony in ecosystems is suitable for use as a teaching tool for students.   Keywords: Interactive Teaching Materials, Cognitive Learning Outcomes, Science, Open Educational Resources, Fifth Grade Students